Glutathione peroxidase‐like enzymes cover five distinct cell compartments and membrane surfaces in Arabidopsis thaliana - Attacha, Safira; Solbach, David; Bela, Krisztina; Moseler, Anna; Wagner, Stephan; Schwarzländer, Markus; Aller, Isabel; Müller, Stefanie J.; Meyer, Andreas J. (Plant, cell and environment, 2017)
Glutathione peroxidase‐like enzymes (GPXLs) constitute a family of eight peroxidases in Arabidopsis thaliana. In contrast to the eponymous selenocysteine glutathione peroxidases in mammalian cells that use glutathione as electron donor, GPXLs rely on cysteine instead of selenocysteine for activity and depend on the thioredoxin system for reduction. Although plant GPXLs have been implicated in important agronomic traits such as drought tolerance, photooxidative tolerance and immune responses, there remain major ambiguities regarding their subcellular localization. Because their site of action is a prerequisite for an understanding of their function, we investigated the localization of all eight GPXLs in stable Arabidopsis lines expressing N‐terminal and C‐terminal fusions with redox‐sensitive green fluorescent protein 2 (roGFP2) using confocal microscopy. GPXL1 and GPXL7 were found in plastids, while GPXL2 and GPXL8 are cytosolic nuclear. The N‐terminal target peptide of GPXL6 is sufficient to direct roGFP2 into mitochondria. Interestingly, GPXL3, GPXL4 and GPXL5 all appear to be membrane bound. GPXL3 was found exclusively in the secretory pathway where it is anchored by a single N‐terminal transmembrane domain. GPXL4 and GPXL5 are anchored to the plasma membrane. Presence of an N‐terminal myristoylation motif and genetic disruption of membrane association through targeted mutagenesis point to myristoylation as essential for membrane localization. Although plant glutathione peroxidase‐like enzymes (GPXLs) have been implicated in important agronomic traits such as drought tolerance, photooxidative tolerance and immune response, there are still major ambiguities regarding their subcellular localization. This gap in our knowledge is closed by this work in which we show the targeting of fluorescent fusion proteins for all eight GPXL family members in Arabidopsis thaliana to the cytosol, nucleus, plastids, mitochondria and the secretory pathway, respectively. By using redox‐sensitive green fluorescent protein 2 as a probe, we show that GPXL3 in contrast to earlier assumptions is not in the cytosol or mitochondria but rather localized in the secretory pathway as a membrane‐bound protein anchored with a transmembrane domain. Furthermore, we provide evidence that two other GPXLs, GPXL4 and GPXL5, are anchored to the plasma membrane through myristoylation of the N‐terminus.